Estimating bull and bear betas for the Nigerian stock market using logistic smooth threshold model - Mohammed M. Tumala; OlaOluwa S. Yaya (CBN Journal of Applied Statistics, 2015)
In this paper, we examine the Nigerian stock market sector returns and estimate the bull and bear betas using the Logistic Smooth Threshold Market (LSTM) model. The LSTM model specification follows from the linear Constant Risk Market (CRM) model. We estimate the LSTM model for the overall sampled daily time series from 2001 to 2012 using the conditional nonlinear least squares approach. We also estimate the model for each of the All share Index (ASI) sub-samples taking the time of financial crisis (February 2008) as the break point. The results show the significant correlations of stocks returns in each market industry with ASI. Nonlinear LSTM dynamics are found to be significant, with significant bull and bear betas in the overall and each of the sub-samples. We find in particular, that the Petroleum, Finance, and Food and Beverages sector equities to be of higher investment risk within the study period.
Keywords: C22; C58; 330; Logistic smooth threshold model; nonlinear least squares; market beta; market returns